Computational testing of trivalent dopants in CeO2 for improved high-kappa dielectric behaviour - WATSON, GRAEME (My University, 2013)
Due to its high dielectric constant, large band gap, and very small lattice mismatch with Si, CeO 2 has been proposed as a promising candidate high- k dielectric material. The performance of CeO 2 as a dielectric material, however, is severely limited due its propensity for facile reduction (oxygen vacancy formation), which causes a high interface state density, and subsequent decreased drain currents. In this article we use density functional theory (DFT) to screen for trivalent dopants which could decrease the concentration of defects in CeO 2 samples. We demonstrate that La and Y are the most soluble trivalent dopants in CeO 2 , and can reduce the number of the electrons in the system both ionically (formation of [M Ce ? V O ? M Ce ] clusters) or to a lesser extent electronically (hole formation). La doping also increases the lattice constant of CeO 2 , improving the lattice match with Si
PUBLISHED
Keywords: Si, CeO 2; Si, CeO 2